Adherence to PrEP Among Young Men Who Have Sex With Men Participating in a Sexual Health Services Demonstration Project in Alameda County, California. (1st August 2019) - Myers, Janet J.; Kang Dufour, Mi-Suk; Koester, Kimberly A.; Udoh, Ifeoma; Frazier, Remi; Packard, Rebecca; Kennedy, Kristin; Erguera, Xavier; Horowitz, Jessica; Grant, Robert; Burack, Jeffrey H.
Abstract : Background: Young men of color who have sex with men face a continual increase in rates of HIV infection. Pre-exposure prophylaxis (PrEP) is an important prevention method for these young men. Setting: The Connecting Resources for Urban Sexual Health (CRUSH) demonstration project provided sexual health services, including PrEP, to young men who have sex with men aged 18–29 years. We report on adherence and factors influencing it. Methods: Participants were offered HIV and sexually transmitted infection testing, prevention counseling, PrEP, and when appropriate, sexually transmitted infection treatment and postexposure prophylaxis. Participants taking PrEP had erythrocyte tenofovir diphosphate and emtricitabine levels measured through dried blood spot testing at 4, 12, and 24 weeks to estimate medication adherence. Participants also completed surveys to assess demographic and psychosocial measures. Results: From February 2014 to November 2015, CRUSH enrolled 257 participants. Ninety-three percent started PrEP, 81% of whom initiated it at their first visit. Twelve percent required postexposure prophylaxis before starting PrEP. Adherence at protective levels was initially high with 87% demonstrating levels consistent with at least 4 doses per week at week 4, compared with 77% at the 48-week follow-up. African American race, exposure to violence, and having survival needs were associated with significantly lower levels of adherence [odds ratio (OR): 0.33; confidence interval (CI): 0.11 to 0.97, P < 0.04; OR: 0.79; CI: 0.59 to 1.04, P < 0.10; OR: 0.51; CI: 0.24 to 1.05, P < 0.07]. Conclusions: Most young men who initiate PrEP adhere at levels that confer protection against HIV infection. Interventions should account for differences in life experiences, particularly addressing the structural challenges facing young African American men.